DDRE-13. DECONVOLUTING MECHANISMS OF RESISTANCE TO BRAF INHIBITORS IN BRAF V600E HUMAN GLIOMA. (9th November 2020) - Schreck, Karisa; Morin, Andrew; Zhao, Guisheng; Sanford, Bridget; Green, Adam; Jones, Kenneth; Banerjee, Anurhada; Nazemi, Kellie; Samuel, David; Kilburn, Lindsay; Solomon, David; Pratilas, Christine; et al.
Abstract: BACKGROUND: While BRAF-targeted therapy can be effective in a subset of patients with glioma, resistance to treatment can emerge over time. The description and validation of mechanisms of resistance in BRAF-mutant glioma are not previously described. METHODS: Pre- and post- BRAF inhibitor (BRAFi) or BRAFi/MEK inhibitor (MEKi) treated patient samples were obtained under IRB-approved protocols at University of Colorado Denver, UCSF, and Johns Hopkins. Targeted DNA sequencing or whole exome sequencing (WES), and RNA-seq were conducted on paired samples. Functional validation of putative resistance mechanisms was performed using established glioma cell lines with BRAF V600E mutation (DBTRG-5MG, AM38, B76). RESULTS: Analysis of 15 tissue sample pairs identified point mutations in 15 genes (including CBL, NF1, PTEN, and MAP2K1 ) and expression changes in RAF1 leading to putative mechanisms of resistance. We performed functional validation of loss of NF1 and CBL as resistance mechanisms and demonstrated growth inhibition and cell death in response to BRAFi with siRNA/sgRNA -mediated knockdown of each gene. Knockdown of CBL resulted in increased EGFR expression and phosphorylation, a possible mechanism for maintaining ERK signaling within the cell. Combination therapy with a MEKi or EGFR inhibitor was able to overcome resistance to BRAFi, in NF1 knockdown and CBL knockdown, respectively. Restoration of wild-type PTEN in B76 cells (PTEN-/-) restored sensitivity to BRAFi. Ingenuity pathway analysis suggested that a switch from BRAF to CRAF dependence mediated resistance in some tumors. Indeed, inhibition of CRAF expression using siRNA in a patient-derived glioma cell line re-sensitized cells to BRAFi. CONCLUSIONS: Analysis of pre-/post-treatment BRAF mutant glioma sample pairs, primarily from pediatric patients, identified a variety of putative resistance mechanisms, some of which have been validated in vitro . Resistance mechanisms to BRAFi in glioma are varied and may be susceptible to different combinations of targeted therapy, highlighting the importance of a personalized approach.